PENGUNGKAPAN CSR PERBANGKAN SYARIAH SEBAGAI KEBUTUHAN INFORMASI STAKEHOLDER - Rinovian, Reztu; Suarsa, Abin (2018)
This research aims to analyze the disclosure of corporate social responsibility by Bank Syariah Mandiri dan Bank Syariah Bukopin based on shariah enterprise theory. This research wasconducted by analyzing how the Bank Syariah Mandiri dan Bank Syariah Bukopin disclose corporate social responsibility through the information presented in the annual report are based on the items disclosure of social responsibility based on sharia enterprise theory. This research uses a qualitative method with case study method in which the analysis using content analysis. The data used in this research is secondary data in the form of a written document that is the annual report of Bank Syariah Mandiri dan Bank Syariah Bukopin obtained from the official website of Bank Syariah Mandiri dan Bank Syariah Bukopin. This research is descriptive interpretative to discuss problems with clear descriptions based on the ability of researchers to reveal the purpose of understanding the information presented in the annual report of Bank Syariah Mandiri dan Bank Syariah Bukopin. This research shows that social responsibility reporting Bank Syariah Mandiri dan Bank Syariah Bukopin still very limited, and is far from being in accordance with sharia enterprise theory.